Evaluating cervical deformity corrective surgery outcomes at 1-year using current patient-derived and functional measures: are they adequate? - Passias, Peter G. (J Spine Surg, 2018)
BACKGROUND: Current health-related quality of life (HRQL) metrics used to assess patient outcomes following surgical correction of cervical deformity (CD) are not deformity-specific and thus cannot capture all aspects of a patient’s deformity and outcomes. The purpose of this study is to evaluate the sensitivity of different HRQL outcome measures in assessing CD patients’ outcomes 1-year post-operatively. METHODS: Retrospective review of prospective multi-center database. Inclusion criteria: CD patients ≥18 yrs with pre- and 1-year post-operative radiographs and HRQLs [modified Japanese Orthopaedic Association (mJOA), EuroQol five-dimensions (EQ-5D), neck disability index (NDI)]. Associations between changes in EQ5D and NDI with improvement at 1-year in mJOA scores were assessed by whether or not the patient met the minimum clinically important difference (MCID) as well as whether or not they improved by one or more categories (i.e., change from moderate to mild). Odds ratios reported with 95% confidence intervals. RESULTS: Sixty-three CD patients were included (mean 62 y, 55.6% F). Average baseline NDI scores were 46.75, mJOA was 13.68, and EQ-5D 0.74. Overall baseline myelopathy breakdown: none—9.5%, mild—30.2%, moderate—42.9%, high—17.5%. At 1-year, 46% of patients improved in mJOA, 71.4% NDI, and 65.1% EQ-5D. 19% of patients met mJOA MCID, 44.4% NDI MCID, 19% EQ-5D MCID. One-point improvement in NDI increased the odds of mJOA improvement and reaching mJOA MCID (improvement: OR, 1.06, CI: 1.01–1.10, P=0.01; MCID: OR, 1.06, CI: 1.02–1.11, P=0.006). Improvement in EQ-5D by 0.1 increased the odds of improving in mJOA and reaching mJOA MCID at 1-year (improvement: OR, 3.85, CI: 1.51–9.76, P=0.005; MCID: OR, 3.88, CI: 1.52–9.88, P=0.005). While correlations exist between outcome measures, when modeling these outcomes while controlling for confounders including cSVA change, surgical invasiveness, age and CCI, these HRQLs were not strongly correlated. CONCLUSIONS: Improvements in functional outcomes, as defined by mJOA score, were correlated with changes in neck based disability and general health state, defined by NDI and EQ-5D respectively. In an adjusted model, however, these direct relationships were not maintained. A CD-specific HRQL might be more useful for surgeons in assessing patient outcomes using a single metric.